Genetic variation and phylogeography of the wild yeast Saccharomyces paradoxus in Eurasia - Almeida, Pedro Miguel Coelho de (2012)
Tese de mestrado. Biologia (Microbiologia Aplicada). Universidade de Lisboa, Faculdade de Ciências, 2011